ANALYSIS OF EMPLOYEE WORK PERFORMANCE ASTON SAMARINDA HOTEL & CONVENTION CENTER - Muhamad Harry Rahmadi; Bun Yamin; Nita Rislawati; Joko Sabtohadi (Jurnal Scientia, 2023)
This study aims to determine the application of job promotions and position mutations that occur at Aston Samarinda Hotel & Convention Center, and how much influence the position promotion and position mutations have on the work performance of Aston Samarinda Hotel & Convention Center employees. The method used is descriptive method. The reason for using this method is to describe or describe the condition of the company systematically, factually, accurately and credibly regarding the object of research. To measure and analyze the influence between variables the authors spread to 85 respondents to employees of Aston Samarinda Hotel & Convention Center.